The City Walls of Athens (5th c. BC – 18th c. AD): a Contemporary Approach - Vizyinou, Ourania (Journal of Greek Archaeology, 2018)
In modern-day Athens the fortification walls, built both in ancient times and subsequent periods, are not currently noticeable to the casual observer, despite having defined for long periods the city’s life. In fact, the majority of modern Athenians and visitors do not know of their existence since their remains are inconspicuous as a result of aggressive modern building schemes. While these remains are not materially magnificent, they are so historically as a mirror of the city’s fate.